The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1073/pnas.1002325107
|View full text |Cite
|
Sign up to set email alerts
|

A super-resolution map of the vertebrate kinetochore

Abstract: A longstanding question in centromere biology has been the organization of CENP-A-containing chromatin and its implications for kinetochore assembly. Here, we have combined genetic manipulations with deconvolution and super-resolution fluorescence microscopy for a detailed structural analysis of chicken kinetochores. Using fluorescence microscopy with subdiffraction spatial resolution and single molecule sensitivity to map protein localization in kinetochore chromatin unfolded by exposure to a low salt buffer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
217
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(234 citation statements)
references
References 49 publications
10
217
0
Order By: Relevance
“…In human cells CENP-C centromere recruitment is reduced after replacement of CENP-A with H3/CENP-A chimeras lacking the carboxy-terminal CENP-A region (Fachinetti et al 2013). S. cerevisiae CENP-C Mif2 dimerizes through a region near its carboxyl terminus (Cohen et al 2008), presenting the possibility of a CENP-C dimer interacting with a CENP-A octameric nucleosome, or higher-order structures involving two CENP-A nucleosomes, consistent with suggestions that CENP-C is important for higher-order centromere structure (Ribeiro et al 2010).…”
Section: The Centromeresupporting
confidence: 73%
See 1 more Smart Citation
“…In human cells CENP-C centromere recruitment is reduced after replacement of CENP-A with H3/CENP-A chimeras lacking the carboxy-terminal CENP-A region (Fachinetti et al 2013). S. cerevisiae CENP-C Mif2 dimerizes through a region near its carboxyl terminus (Cohen et al 2008), presenting the possibility of a CENP-C dimer interacting with a CENP-A octameric nucleosome, or higher-order structures involving two CENP-A nucleosomes, consistent with suggestions that CENP-C is important for higher-order centromere structure (Ribeiro et al 2010).…”
Section: The Centromeresupporting
confidence: 73%
“…One possibility is that binding of CENP-S/X to CENP-T/W confers some centromere-specific function, but the ability of CENP-T to function independently from CENP-S suggests CENP-T/W/S/X does not form an obligate nucleosome-like particle (Hori et al 2008a;Amano et al 2009). Indeed, before identification of the CENP-T/W/S/X tetramer, CENP-T/W was suggested to associate primarily with histone H3 rather than CENP-A (Hori et al 2008a;Ribeiro et al 2010). Consistent with this, although CENP-T is lost from centromeres completely lacking CENP-A, its centromere levels are largely unaffected by a 90% CENP-A reduction (Fachinetti et al 2013).…”
Section: Histone Modificationsmentioning
confidence: 90%
“…Previous characterisation of centrochromatin had shown that levels of H3K9ac are low in this region (Bergmann et al, 2011;Sullivan and Karpen, 2004), and, at least in chicken kinetochores, we had been able to detect H3K9me3 interspersed within the overall domain of CENP-A binding by using super-resolution microscopy (Ribeiro et al, 2010). Following the binding of p65, which contains the 30 amino acid transcription activation domain of NF-kB subunit p65, kinetochore-associated alpha-satellite DNA underwent an ,10-fold increase in transcription, although importantly the transcription levels remained far below those observed at a control euchromatic locus.…”
Section: Discussionmentioning
confidence: 64%
“…Besides CENP-A, active centromeres display a specific profile of post-translational modifications on their associated histone H3-containing nucleosomes (Bergmann et al, 2011;Lam et al, 2006;Ribeiro et al, 2010;Sullivan and Karpen, 2004). This special chromatin, which has been termedx 'centrochromatin' (Sullivan and Karpen, 2004), suggests a functional link between the local chromatin environment and kinetochore function.…”
Section: Introductionmentioning
confidence: 99%
“…It will now be important to integrate these results with a dynamic picture of CenH3 loading (15). New, super-resolution microscopy methods (16), careful assembly of satellite DNA arrays (9,17), and comparative studies of different organisms will help with answering the long-standing questions of what defines a centromere. How and when is the DNA underlying the centromeric nucleosomes defined in the cell?…”
mentioning
confidence: 99%